RESEARCH COLLABORATION ON THE DEVELOPMENT OF IUIU MAIN CAMPUS MASTER PLAN : TOWARDS 2035 CAMPUS DEVELOPMENT AGENDA - Syed Iskandar Ariffin, editor 647843; Ismail Simbawa Gyagenda, editor 647844; Khairul Anwar Mohamed Khaidzir, editor 334603; Jamilia Mohd Marsin, managing editor 647845; Ayub Kasujja, associate editor 647846; Dauda Semujju, associate editor 647847; Kajumba Mickdad, associate editor 647849; Kibirige Uthman, associate editor 647851; Kinsambwe Rashid, associate editor 647853; Muhamad Zaly Muhammad Hussein, associate editor 647855; Muhammad Farid Azizul Azizui, 1985-, associate editor 503859; Muhammad Wassajja, associate editor 647856; et al. (Johor Bahru, Johor : Institut Sultan Iskandar, UTM, 2021)
Includes bibliographical references.